1998
DOI: 10.1055/s-1998-5932
|View full text |Cite
|
Sign up to set email alerts
|

Norcaradienes from the Intramolecular Cyclopropanation Reactions of Diazomethyl Ketones. Valuable Intermediates for the Synthesis of Polycyclic Diterpenes

Abstract: The intramolecular cyclopropanation reactions of the aromatic ring in tetrahydronaphthyl diazomethyl ketones initiated by rhodium(II) and copper(II) derived transition metal catalysts afford stable norcaradiene products. Further elaboration has led to pentacyclic structures that have considerable potential for the expeditious synthesis of complex polycyclic diterpenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Second, the norcaradiene must be formed under conditions where it is precluded from undergoing electrocyclic ring opening to generate the corresponding heptatriene. The central chemoselectivity issue, with regard to cyclopropanation and C–H insertion, had been previously examined by Mander and co-workers in an elegant total synthesis of gibberellin GA 103 . In these studies, the authors discovered that both the nature of the metal catalyst and the arene substitution pattern influence the reaction outcome.…”
Section: Recent Applications In Total Synthesismentioning
confidence: 99%
“…Second, the norcaradiene must be formed under conditions where it is precluded from undergoing electrocyclic ring opening to generate the corresponding heptatriene. The central chemoselectivity issue, with regard to cyclopropanation and C–H insertion, had been previously examined by Mander and co-workers in an elegant total synthesis of gibberellin GA 103 . In these studies, the authors discovered that both the nature of the metal catalyst and the arene substitution pattern influence the reaction outcome.…”
Section: Recent Applications In Total Synthesismentioning
confidence: 99%
“…The propensity of norcaradiene moieties to undergo retro-6π-electrocyclizations to form cycloheptatrienes made the isolation of such a structure from nature truly remarkable. In the late 19th century, Buchner had published reports of the reaction of diazocarbonyls with benzene, , although they had only scarcely been employed in total synthesis. , In their 2011 total synthesis of salvileucalin B (Scheme ), Reisman and co-workers successfully developed conditions to access the norcaradiene core . Ultimately, it was found that treatment of diazonitrile 53 - 1 with Cu­(hfacac) 2 at 120 °C under microwave irradiation provided the hexacyclic core ( 53 - 2 ) in 65% yield.…”
Section: First-row Metal Carbenoidsmentioning
confidence: 99%
“…Modes of reactivity include cyclopropanation, C−H insertion, heteroatom-H insertion, and ylide generation. Arene substrates, in particular, participate in cyclopropanation, benzylic C−H insertion, and aryl C−H insertion reactions, and this methodology has been elegantly applied in natural product synthesis. , Chromium complexation dramatically alters the reactivity of aromatic systems . The electron-withdrawing chromium tricarbonyl moiety enhances nucleophilic addition 3a,e to complexed arenes and also acts to increase the acidity of aryl 3b,f and benzylic 3c, hydrogens.…”
mentioning
confidence: 99%
“…Intramolecular Buchner reactions are also reported in the literature. 2a,e, In particular, Doyle and co-workers used rhodium-catalyzed reactions of N -benzyldiazoacetamides to synthesize fused 5,7-ring systems . These substrates inspired an intramolecular competition experiment to compare directly the effect of chromium tricarbonyl complexation on cyclopropanation using pseudo- C 2 symmetric substrate 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation